yes
2007-02-27 16:52:08
·
answer #1
·
answered by Shawn J 3
·
0⤊
0⤋
2x + y = 180
x + 3y = 180
Then y = 180 - 2x
Substitute
x + 3(180 - 2x) = 180
x + 540 - 6x = 180
-5x = -360
x = 72
Since x = 72; then y = 36. (72 + 3y = 180, solve for y)
2007-02-27 16:53:18
·
answer #2
·
answered by nothereanymoreomgteh 4
·
0⤊
0⤋
Multiply one of the problems to get either the x or the y to cancer out. You could multiply the bottom x and the whole problem by -2 to get a:(-2x+3y= -360) then when you add them together, the X's cancer out because (+2) subtract a (-2) would give you a 0. you are them left with:-2y=(-180)You divide both sides with -2. The ( -2) cancers out on both sides leaving it with (y=90).If you want to solve for x, you have to pick one, like 2x+y=180. plug in the 90 for y. To get 2x+90=180. subtract the 90 from 180 to get 2x =90. Divide 90 by 2, you'll get x=45
Now you can get Ur problem right: (x=45), (y=90)
2007-02-27 18:07:20
·
answer #3
·
answered by vvn 3
·
0⤊
0⤋
2x+y=180
x+3y=180
so
2x+y=x+3y x=2y put this in one of the equations
2(2y)+y=180 4y+y=180 5y=180 y=36
2x+36=180 2x=144 x=72
2007-02-27 17:46:27
·
answer #4
·
answered by reza 2
·
0⤊
0⤋
since you have a system of equations here you can eliminate one variable and solve.
2x+y=180
x+3y=180
I'll start by eliminating x
Multiply the bottom equation by -2
this gives us
2x+y=180
-2x-6y=-360
now you can see that when we add the equations the x's cancel out and we are left with
-5y =-180
y = 36
now we can plug the value for y into either one of the equations to solve for x
using the first equation 2x + 36 = 180
2x= 144
x= 72
so there are your values for x and y
2007-02-27 17:04:34
·
answer #5
·
answered by Tom M 3
·
0⤊
0⤋
Convert these equations into slope-intercept form(y=mx+b), graph them, and find the point of intersection.
2x+y=180
2x+y-2x=180-2x
y=180-2x
y=-2x+180
x+3y=180
x+3y-x=180-x
3y=180-x
(3y)/3=(180-x)/3
y=60-(1/3)x
y=-(1/3)x+60
Graph the 2 lines on one coordinate plane, and there you go!
2007-02-27 16:59:49
·
answer #6
·
answered by _anonymous_ 4
·
0⤊
0⤋
2x + y = 180 - e1
x + 3y = 180 - e2
Therefore,
from e2,
x = 180 - 3y - e3
sub e3 into e1
2(180 - 3y) + y = 180
360 - 6y +y = 180
-5 y = -180
y = 180 / 5 = 36
y = 36
so, use y = 36 into e3
x = 180 - 3y
x = 180 - 3(36)
x = 72
2007-02-27 17:11:35
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
(3x-5)/4 +x/2 = a million/3 {(3x-5)*2 + (x*4)}/8 = a million/3 (6x-10+4x)/8 = a million/3 10x - 10 = 8/3 10x= (8/3)+10 10x= 38/3 x= 38/30 x= 19/15 or a million.26 * refers to multiplication / refers to branch
2016-09-30 00:18:25
·
answer #8
·
answered by schiraldi 4
·
0⤊
0⤋
multiply the second eqn by 2
so 2x+6y=360 -1
other eqn is 2x+y =180 -2
subract 1-2
so 2x+6y-2x-y = 360 -180
5y=180
y=36
x=180-3(36)
x=72
2007-02-27 16:53:40
·
answer #9
·
answered by vaidehi 2
·
0⤊
0⤋
set each problem so that they are both equal to y
180- 2x=y
(180-x)/3 = y
then set the equations equal to each other
180-2x= (180-x)/3 and solve for x
do the same thing with y( starting at step one!)
2007-02-27 16:53:44
·
answer #10
·
answered by JOEY/ KATH K 2
·
0⤊
0⤋